Phenotypic Suppression by Streptomycin of Amber Mutants in the Ribonucleic Acid Bacteriophage Coat Protein Cistron - Kuwano, Michihiko (1969)
After mutagenesis with nitrosoguanidine or ultraviolet light, 298 streptomycin high-resistant and 98 streptomycin high-dependent mutants were isolated from HfrC Su(−). They were tested for their ability to phenotypically suppress five different amber ribonucleic acid (RNA) bacteriophage mutants in the presence of streptomycin. The phage mutants are all in the coat protein, which is 129 amino acids long; the uracil-adenine-guanine codons were at the following positions: sus3 and amB2, 6; amB11, 50; amB21, 54; sus11, 70. Only sus3 and amB2 could be phenotypically suppressed by streptomycin; this was clearly demonstrated in nine mutant strains, seven str-HR and two str-HD. The suppression was always dependent upon added streptomycin and was dose-dependent in all cases. None of the mutants showed measurable suppression in absence of the drug. Among revertants to streptomycin independence from streptomycin-dependent strains that could show phenotypic suppression, most of those that were still resistant to streptomycin (10 μg or more) retained the capacity to show phenotypic suppression; whereas among those revertants sensitive to 10 μg of streptomycin or less, none retained the capacity. Eight different amber polar mutants (strong and weak) in gene 34 of phage T4 were also tested for pleiotypic suppression by streptomycin in all the streptomycin-resistant and -dependent strains isolated. No suppression was found in any of the 396 strains tested.